Examining the J-curve and S-curve patterns in Pakistan’s economic ties with the USA and China, the world’s economic giants - Jing, Jin; Ahmad, Riaz; Usman, Muhammad; Iqbal, Javed; Ahmad, Sareer; Gul, Azeem; Mi, Hong; Abdirasulova, Zhainagul; Mamadievich, Ravshanbek Dzhumaev (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: Since the Jand S-curve concepts were first introduced, several researchers have tried to test their validity through empirical research. To offer recommendations for additional research, this study looked at the relevant literature. Methodology: The idea of the S-curve is an extension of the J-curve, which shows how the trade balance improves over time despite initially being worse due to currency depreciation. According to the S-curve hypothesis, there is a positive cross-correlation between the current exchange rate and the future trade balance of a country, and a negative cross-correlation between the current exchange rate and the past trade balance. To understand the pattern of the relationships, the author considered time series data for fifteen 3-digit industries/commodities between Pakistan and its main trading partners – China and the USA – from 1980 to 2022. Results: The results demonstrate that the minority of Pakistani industries, engaged in trade with the USA and China, supported J and S-curves behaviour. Implications and recommendations: The study showed that improving the trade balance is not always possible with domestic currency devaluation. Originality/Value: This study made an incremental contribution in that it critiqued a consumer price index (CPI) which has been used in literature on the aggregate level, and constructed commodity-based CPI for the analysis.
Argumenta Oeconomica, 2025, Nr 2 (55), s. 233-247
Keywords: USA; S-curve; J-curve; China; currency depreciation; 3-digit industries; Pakistan